Application of Presidential Threshold In Indonesia And Comparison With Several Countries - Muhammad Ali Farhan (Faculty of Law, Merdeka University Surabaya, 2022)
A country is said to be a modern country is the large number of people's participation in regulating and running their country, as well as the existence of general elections in selecting candidates for people's representatives to occupy positions from state positions, therefore each country must have its own arrangements regarding how to obtain a position and the duration of a person or more. in occupying these positions, one of which is the position of president and vice president whose terms of office and the pattern of carrying them often differ between countries, in Indonesia, President Have a Power More than Parliament, Therefore someone or more who wants to hold the office of president and vice president needs to get more than twenty percent of the votes in the seats The House of Representatives, However Not All Countries implement the presidential threshold with a vote of twenty percent the parliament. But it could be more and there are even some countries don’t use this system? And the method I used in this research is Normative Type with conceptual approach and case analysis, because as we known in this world theres a much country who Not applied presidential Threshold system, so in this research I found the country who applying presidential threshold and the reason that county not use that system.